Strongheart : The Lost Journals of May Dodd and Molly McGill - Fergus, Jim; Standing Bear, Molly (Fictitious character) (New York : St. Martin's Griffin, 2021)
"In 1873, a Cheyenne chief offers President Grant the opportunity to exchange one thousand horses for one thousand white women, in order to marry them with his warriors and create a lasting peace. These women, 'recruited' by force in the penitentiaries and asylums of the country, gradually integrate the way of life of the Cheyenne, at the time when the great massacres of the tribes begin. After the battle of Little Big Horn, some female survivors decide to take up arms against the United States, which has stolen from the Native Americans their lands, their way of life, their culture, and their history"--Publisher marketing.
Keywords: Little Bighorn, Battle of the, Mont., 1876 -- Fiction; Cheyenne Indians -- Fiction; Historical fiction; Western fiction